1985
DOI: 10.1111/j.1365-2044.1985.tb10665.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and recovery characteristics of isoflurane and halothane anaesthesia for short outpatient operations in children

Abstract: Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 6 publications
2
20
0
Order By: Relevance
“…The vocalization and marked expiratory efforts which occurred in a minority of rabbits occurred after loss of consciousness, and were probably caused by laryngospasm. This has been reported in children following face-mask induction with isoflurane (Pandit et al 1985), 73 and may also contribute to an increased risk of anaesthetic mortality during induction with volatile anaesthetics in rabbits.…”
Section: Discussionmentioning
confidence: 96%
“…The vocalization and marked expiratory efforts which occurred in a minority of rabbits occurred after loss of consciousness, and were probably caused by laryngospasm. This has been reported in children following face-mask induction with isoflurane (Pandit et al 1985), 73 and may also contribute to an increased risk of anaesthetic mortality during induction with volatile anaesthetics in rabbits.…”
Section: Discussionmentioning
confidence: 96%
“…also reported that isoflurane could be used as an alternative to halothane for rapid inhalation anaesthesia induction [4]. Although isoflurane does not have the potential for hepatic toxicity associated with halothane, it does cause considerably more complications during conventional inhalational induction [6]. Loper rt ul.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, these favorable qualities are accentuated in those volatile anesthetics with lower blood/gas solubility such as isoflurane, sevoflurane, and desflurane making the idea of their use in horses additionally attractive. However, a high incidence of irrational, disoriented behavior has been observed in children emerging from isoflurane and desflurane compared to halothane and sevoflurane 4,5 …”
mentioning
confidence: 99%